2000
DOI: 10.1152/jn.2000.84.3.1627
|View full text |Cite
|
Sign up to set email alerts
|

EEG Correlation of the Discharge Properties of Identified Neurons in the Basal Forebrain

Abstract: The basal forebrain (BF) is a heterogeneous structure located in the ventral aspect of the cerebral hemispheres. It contains cholinergic as well as different types of noncholinergic corticopetal neurons and interneurons, including GABAergic and peptidergic cells. The BF constitutes an extrathalamic route to the cortex, and its activity is associated with an increase in cortical release of the neurotransmitter acetylcholine, concomitant with electroencephalographic (EEG) low-voltage fast activity (LVFA). Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
138
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(151 citation statements)
references
References 47 publications
12
138
1
Order By: Relevance
“…Although other parts of the ARAS, such as the thalamus (3), likely are important, our results suggest that BF PV neurons are involved in state-dependent control of GBO. Juxtacellularly identified BF PV neurons in anesthetized rats increased their firing rate with cortical activation caused by tail pinch (23). Our preliminary recordings from two optically identified BF PV neurons in mice confirmed that their discharge is highest in states that show more GBO activity, i.e., wakefulness and REM sleep.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Although other parts of the ARAS, such as the thalamus (3), likely are important, our results suggest that BF PV neurons are involved in state-dependent control of GBO. Juxtacellularly identified BF PV neurons in anesthetized rats increased their firing rate with cortical activation caused by tail pinch (23). Our preliminary recordings from two optically identified BF PV neurons in mice confirmed that their discharge is highest in states that show more GBO activity, i.e., wakefulness and REM sleep.…”
Section: Discussionsupporting
confidence: 68%
“…Many cortically projecting BF GABAergic neurons contain the calcium-binding protein PV, and a large majority of BF PV neurons are GABAergic (21,22). Recordings from identified BF PV neurons in anesthetized animals revealed they increase their discharge rate during cortical activation induced by sensory stimulation (23). Furthermore,…”
mentioning
confidence: 99%
“…1B). Assessments of the electrophysiological characteristics of Cy3-labeled neurons with cell-attached or whole-cell recordings revealed spontaneous or evoked firing activity similar to that reported previously in BFCNs [40][41][42][43]. In acute brain slices, approximately a third of Cy3-positive cells (6/21; 28.5%) revealed slow and irregular firing under cell-attached recording, with the rest electrically silent (15/21; 71.5%) but firing transiently under depolarizing conditions (30 mM extracellular K + ; data not shown).…”
Section: Resultssupporting
confidence: 79%
“…Throughout the forebrain, Parv ϩ neurons are commonly fast spiking cells, as evident from in vitro and in vivo recording studies of identified neurons (Celio, 1986;Kawaguchi et al, 1987;Kawaguchi, 1993;Kawaguchi and Kubota, 1993;Sik et al, 1995). In the medial septumdiagonal band, Parv ϩ cells have been found to be fast spiking by in vitro recordings (Morris et al, 1999) and in the BF (in one cell) by in vivo recordings (Duque et al, 2000). In our in vivo recording studies, we identified a large number of cortically projecting GAD ϩ neurons that discharge tonically at relatively high rates (average Ͼ 30 Hz) in association with cortical activation (Manns et al, 2000a) and thus could correspond to the cortically projecting, Parv ϩ BF neurons identified here.…”
Section: Functional Significance Of Cbp Content In Bf Cell Groupsmentioning
confidence: 92%